Handbook of research on narrative advertising - Yilmaz, Recep (Business Science Reference, 2019)
"This book examines the use of narration in advertising. It examines narration models, the conceptualization of advertising narration to new media and new media cultures, and narrative theories and practices of advertising discourse and ideology"--